The incidence and effects of decentralized wage bargaining in Finland - Antti Kauhanen; Terhi Maczulskij; Krista Riukula (Journal of Labor Research, 2024)
There was a strong push from employers to decentralize wage setting in Finland in the early 2000s. We analyze the incidence of decentralization and its effect on the level and dispersion of wages by using nationally representative panel data. The results show that wage setting was more likely decentralized in collective agreements where a high share of employees worked in manufacturing or real estate industries than in other industries, such as in education and human health and social work activities. Decentralization was, for the most part, quite short-lived. Using recent difference-in-differences methods that allow for heterogeneous treatment effects and differences in the timing of treatment, we show that decentralization had modest positive effects on the level and dispersion of wages in manufacturing.
Keywords: J31; J51; J52; 330; Collective bargaining; Decentralization; Wage dispersion; Difference-in-differences